2015
DOI: 10.1136/jmedgenet-2014-102797
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year outcome of enzyme replacement therapy with agalsidase beta in patients with Fabry disease

Abstract: BackgroundFabry disease results from deficient α-galactosidase A activity and globotriaosylceramide accumulation causing renal insufficiency, strokes, hypertrophic cardiomyopathy and early demise. We assessed the 10-year outcome of recombinant α-galactosidase A therapy.MethodsThe outcomes (severe clinical events, renal function, cardiac structure) of 52/58 patients with classic Fabry disease from the phase 3 clinical trial and extension study, and the Fabry Registry were evaluated. Disease progression rates fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
234
2
22

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(271 citation statements)
references
References 26 publications
13
234
2
22
Order By: Relevance
“…25 In addition, neutralising antibodies directed against agalsidase-beta may be another factor that may limit the success in controlling proteinuria and/ or stabilising renal function. 26 The importance of the age at which ERT is initiated was recently emphasised 12 and is confirmed by the present findings, suggesting that severe underlying changes in renal structure 21 may limit the beneficial effects of controlling urine protein excretion. Regression analysis (table 4) showed that the age at which ERT was started was the only significant factor associated with risk of renal progression in patients for whom ACE inhibitor or ARB therapy controlled the average UPCR to ≤0.5 g/g, thus confirming and extending the recent report from Germain et al…”
Section: Germain Et Alsupporting
confidence: 67%
See 1 more Smart Citation
“…25 In addition, neutralising antibodies directed against agalsidase-beta may be another factor that may limit the success in controlling proteinuria and/ or stabilising renal function. 26 The importance of the age at which ERT is initiated was recently emphasised 12 and is confirmed by the present findings, suggesting that severe underlying changes in renal structure 21 may limit the beneficial effects of controlling urine protein excretion. Regression analysis (table 4) showed that the age at which ERT was started was the only significant factor associated with risk of renal progression in patients for whom ACE inhibitor or ARB therapy controlled the average UPCR to ≤0.5 g/g, thus confirming and extending the recent report from Germain et al…”
Section: Germain Et Alsupporting
confidence: 67%
“…13 The overall results were similar for the two randomised studies; patients with higher baseline eGFR and lower UPCR had significant preservation of renal function when treated with agalsidase-beta. [11][12][13] We previously demonstrated in a small, open-label single-centre study that treatment with ACE inhibitors or angiotensin receptor blocker (ARB) to maintain UPCR <0.5 g/24 h was associated with stabilisation of renal function even in Fabry patients at high risk for progression of nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Lyginant Agalzidazę alfa ir Agalzidazę beta, akivaizdžių skirtumų tarp fermentų nenustatyta. 2015 m. atlikta Germaino ir kitų patyrusių specialistų iš viso pasaulio apžvalga, kurios metu įvertinti dešimties metų gydymo PFT rezultatai [31]. Tyrimas parodė, kad, skiriant PFT jaunesniame amžiuje ir esant mažesniam organų taikinių pažeidimui, rezultatai geresni nei skiriant vyresniame amžiuje esant didesniam organų pažeidimui.…”
Section: Pakaitinė Fermentų Terapijaunclassified
“…The scientific literature offers several theoretical factors that could contribute to decreased fitness in males with FD including: mechanical blockage of the vas deferens due to glycolipid storage, autonomic dysfunction, reduced life expectancy, depression and decreased social adaptive functioning, or personal choice Wagner et al 2014;Arends et al 2015;Germain et al 2015;Waldek et al 2009). In order to provide accurate genetic counseling about their reproductive fitness to individuals affected by FD, we conducted a multi-center, large scale study to determine if reproductive fitness is decreased in males with FD and, if so, delineate specific risk factors or issues related to decreased fitness.…”
Section: Introductionmentioning
confidence: 99%